A Theoretical Framework Of Quantum Communication Technology Inputance: An Application Technology Readiness And Inputance Model - Mukrim Nurul Hayati Khairulamri; Nor Asiah Yaakub; Noorihsan Mohamad; Mustafa Mohd Hanefah; Rosnia Masruki (2026)
Indexed by MYCITE